Effects of a physical exercise program on university students with burnout syndrome - Ricardo, Yury Rosales (2021)
Doctoral Thesis of the Doctoral Program on Sport Science Branch Physical Activity and Health, supervised by Professor Doctor José Pedro Ferreira, submitted to the Faculty of Sports Sciences and Physical Education of the University of Coimbra.